Supplementation of Trace Mineral in Dry Feed Potential as Immunomodulator Against Aeromonas hydrophila Infection of African Catfish - Putri, Indira Tiffani P; Rizkiantino, Rifky; Windria, Sarasati; Hiroyuki, Andi (Jurnal Veteriner, 2024)
This study explored the potential trace mineral in increasing the immune response of juvenile African catfish (Clarias gariepinus) against the infection caused by Aeromonas hydrophila, which is highly prevalent in aquaculture. The experiment involved five groups that were given different treatments, which consisted of A (negative control), B (positive control), C (2 g/kg of trace mineral in feed), D (4 g/kg of trace mineral in feed), and E (6 g/kg of trace mineral in feed), with each treatment repeated thrice. The experimental fish underwent three days of acclimation before the experimental period, followed by two weeks of treatments in each respective group, and a challenge test by A. hydrophila injection given post-supplementation accompanied by observation, which lasted for a week. The final observation was made on day 8 post-infection, with significant findings revealed in the results. The results showed the survival rate (%) and total leukocyte counts (TLC) of experimental African catfish treated with trace mineral supplementation (groups C, D and E) were remarkably higher than the positive control (group B) after infected by A. hydrophila (P<0.05). Furthermore, groups C and D showed increased lymphocyte and monocyte percentages compared to other treatments (P<0.05). These results indicate that trace mineral supplementation has the potential to be an immunomodulator through its inclusion within the diet of juvenile catfish and its promising effect in boosting their immunity against infection.